360° Videocast as a New Immersive Non-Fiction Audiovisual Genre - Falandes, Carolina Gois [UNESP]; Renó, Denis Porto [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2024)
This study focuses on examining the reports disseminated by the journalism department of Record tv (Brazil) supported by spherical images, “Viagem ao continente gelado” and “Maratona de Jerusalem”, 2023, which stand out for exploring a new immersive non-fiction audiovisual genre, the 360° videocast. This style is inspired by the premises of podcasts and videocasts, forms of entertainment that have received greater attention in recent times. In methodological terms, the research is classified as a multiple case study, based on the interpretation of the transmedia structure of the products and the choices related to the 360° language, also based on interviews given to professionals from the television network. In the literature review section, contributions related to convergence in the television environment, interactivity, broadcast journalism and its connections with immersive content are presented. Among the results achieved, it was possible to determine that the works evaluated show different arrangements, but that they are connected through the exploration of qr codes, cross-platform strategies and a new storytelling model, the 360° podcast/videocast. This is an option that adds to the range of possibilities existing in the field of spherical non-fiction storytelling, being capable of enriching the audience’s informative experience.
El videocast 360° como nuevo género audiovisual inmersivo de no ficción
O VIDEOCAST 360° COMO NOVO GÊNERO DO AUDIOVISUAL IMERSIVO DE NÃO FICÇÃO
Keywords: 360° videocast; broadcast journalism; Communication; qr code; transmedia storytelling